Otoritas, Keberlanjutan dan Perubahan Fikih Dalam Pandangan Wael B. Hallaq - Muhammad Rofiq (Universitas Ahmad Dahlan, 2016)
The existence of fiqh becomes one of the intellectual and integrated treasures in thedaily practices of Moslem. Thus, it has been internalized in the understanding of both the authors and the readers. The existence of fiqh that has been rooted since the beginning of Islam to the recent days has encouraged many scholars to study, research, and conduct several explorations. One of the scientists who are concerned about studying Islamic law is Wael, an orientalist whom views are considered to be sympathetic to Islam. In the study of fiqh, Wael presents new findings related to the authority and sustainability of Islamic law in the framework of madhhabs that he has studied. He concluded that the stagnation of Islamic law has never occurred. Indeed, it continues its progress from time to time. According to him, the statement that the door of ijtihad of having been closed is wrong. Thence, it becomes new thing in the intellectual world of Islam, which was once known as experiencing stagnation with the closing of ijtihad. Wael B. Hallaq examined specifically through intellectual work in three madhhabs of Islamic law, namely Thabaqat with historical analysis. He found a hierarchy of authority madhhab followers that he broke down from Thabaqat Maliki, Shafi'i and Hanafi.However, the established new characteristics which he discovered by shifting anti-taklid paradigm in Islamic law. The division of authorities that he described can be seen as a positive side of taklid. It becomes the point of the criticism, in which talkid should be the parameter of stagnation or sustainability of the law madhhabs in Islam. Therefore, the study conducted by Wael needs to be interconnected using other approaches to make it into amore comprehensive corrections.